Síntese estereosseletiva de bis- e tris-calcogenetos vinílicos mistos - Schneid, Caroline Cassalha Schneider (2007)
In the work presented herein we describe the reaction of diorganoyl dichalcogenides with terminal alkynes under catalyst free conditions, by one pot procedure, to prepare unsymmetrical bis- and tris-chalcogenide alkenes selectively, avoiding the previous preparation of chalcogenealkynes. The reaction proceeded cleanly under mild reaction conditions and the addition of dichalcogenides to alkynes occurred stereoselectively to give exclusively the corresponding Z isomers. The selectivity control of reaction was governed by the effective participation of the hydroxyl group from propargyl alcohols. Indeed, unsymmetrical bis-chalcogenide alkenes were obtained with propargyl alcohol having the acidic hydroxyl group hydrogen. On the other hand, unsymmetrical tris-chalcogenide alkenes were exclusively obtained from alkynes with no potentially acidic hydroxyl group hydrogen.